Complexité de l’agir : une présence qui engage les émotions - Joëlle Libois (Sociétés et Jeunesses en Difficulté)
The emotional dimension linked to the work of the social workers is now little reflected, whether from the point of view of the actors as of the institutions. Emotion is most often thought of as something internal to the individual, carrying risk, overflowing, invading, which must be managed. We postulate that within the framework of the practice, to seize the emotional experience is an educational tool available and performing. Relying on the concept of presence leads us to look at the professional posture and thus on a support that makes professionalism through emotional and relational involvement. Presence is thus understood as the consubstantial of co-presence, as a complex reality, always in motion, which articulates the intentional, interactional and communicational dimensions. She would be in itself performative of the complexity to act him.